Study of the Nuclear Structure for Some Target Nuclei Used in the Production of Beta-Emitting Radioactive Isotopes for the Fabrication of Nuclear Batteries - Alzubadi, Ali A.; Nassir, Samaa S. (Iraqi Journal of Science, 2021)
The nuclear structure of 40Ar, 112Cd, 133Cs, 151Eu, 154Sm, and 226Ra target nuclei used in nuclear battery technology was investigated. These nuclei are widely used for the radioisotope thermo-electric generator space studies and for betavoltaic battery microelectronic systems. For this purpose, some nuclear static properties were calculated. In particular, the single particle radial nuclear density distribution, the corresponding root mean square radii, neutron skin thicknesses, and binding energies were calculated within the framework of Hartree-Fock approximation with Skyrme interaction. The bremsstrahlung spectra produced by the absorption of beta particles through the betavoltaic process and backscattered photons spectrum were also studied. All the obtained results were compared with available experimental data.